Genomic Epidemiology of Salmonella Infantis in Ecuador: From Poultry Farms to Human Infections - Mejía, Lorena; Medina, José Luis; Bayas, Rosa; Salazar, Carolina Satan; Villavicencio, Fernando; Zapata, Sonia; Matheu, Jorge; Wagenaar, Jaap A.; González-Candelas, Fernando; Vinueza-Burgos, Christian (Frontiers in Veterinary Science, 2020)
Salmonella enterica is one of the most important foodborne pathogens around the world. In the last years, S. enterica serovar Infantis has become an important emerging pathogen in many countries, often as multidrug resistant clones. To understand the importance of S. enterica in the broiler industry in Ecuador, we performed a study based on phenotypic and WGS data of isolates from poultry farms, chicken carcasses and humans. We showed a high prevalence of S. enterica in poultry farms (41.4%) and chicken carcasses (55.5%), but a low prevalence (1.98%) in human samples. S. Infantis was shown to be the most prevalent serovar with a 98.2%, 97.8% and 50% in farms, foods and humans, respectively, presenting multidrug resistant patterns. All sequenced S. Infantis isolates belonged to ST32. For the first time, a pESI-related megaplasmid was identified in Ecuadorian samples. This plasmid contains genes of antimicrobial resistance, virulence factors, and environmental stress tolerance. Genomic analysis showed a high homology of S. Infantis strains in the three analyzed components. The results from this study provide important information about genetic elements that help understand the molecular epidemiology of S. Infantis in Ecuador.